A characteristic inlet boundary condition for compressible, turbulent, multispecies turbomachinery flows. (15th January 2019) - Odier, Nicolas; Sanjosé, Marlène; Gicquel, Laurent; Poinsot, Thierry; Moreau, Stéphane; Duchaine, Florent
Highlights: A characteristics inlet boundary condition is proposed for turbomachinery unsteady compressible simulations. This formulation imposes total pressure and temperature, flow direction, species composition. Its acoustic properties are evaluated. The compatibility with turbulence injection while being acoustically non- reflecting is assessed. This condition is finally tested on a rotor/stator turbine stage. Abstract: A methodology to implement non-reflecting boundary conditions for turbomachinery applications, based on characteristic analysis is described in this paper. For these simulations, inlet conditions usually correspond to imposed total pressure, total temperature, flow angles and species composition. While directly imposing these quantities on the inlet boundary condition works correctly for steady RANS simulations, this approach is not adapted for compressible unsteady Large Eddy Simulations because it is fully reflecting in terms of acoustics. Deriving non-reflecting conditions in this situation requires to construct characteristic relations for the incoming wave amplitudes. These relations must impose total pressure, total temperature, flow angle and species composition, and simultaneously identify acoustic waves reaching the inlet to let them propagate without reflection. This treatment must also be compatible with the injection of turbulence at the inlet. The proposed approach shows how characteristic equations can be derived to satisfy all these criteria. It is tested on several cases, ranging from a simple inviscid 2D duct to a rotor/stator stage with turbulence injection.